(3afhf GdcJGHI GdUMajI h GdYedjGJ GdEOQGcjI dOi GdbQGA (B/s - (3Ydj, YHO GdQMjes ((3GdbGgQI (B:s (3GjJQGc ddfTQ h GdJhRjY ,s, 2003)
(3jMGhd gPG GdcJGH GNJjGQ GdYdGbI Hjf GdCTcGd GdUMajI GdNHQ (B-(3GdMOjK (B- (3GdJMbjb(B- (3GdebGd (B- (3GdJbQjQ h Hjf GfJHGg GdbQGA dgPG GdGTcGd h EOQGcge ddaQhb HjfgG h JPcQge ddeYdheGJ GdJj JbOe ef NdGdgGh Pdc ef NdGd GdNUGFU GdeNJdaI dcd Tcd UMaj h GdNUGFU GdOjehLQGajI ddbQGA(B...(3h aj GWGQ Pdc bGe GdcGJH HJUeje h GYOGO ebjGS ddGfJHGg ddafhf GdUMajI h GOQGcgG h WHb GdebjGS Ydi YjfI ebOGQgG GQHYeGFI eaQOI ef GdLeghQ GdbGQF ddUMa Ke GYGO JWHjb GdebjGS eQI GNQi Ydi eLehYI UZjQI ef GdbQGA HdZJ GQHYhf eaQOI h Pdc HGSdhH GdebGHdI GdLeGYjI GdeQcRI h bO MGhd GdcGJH QUO GdNUGFU GdGOQGcjI dcd af UMaj Ydi MOg h GdYhGed GdJj JSGYO Ydi GOQGcg h JPcQg h GMJjGLGJ GdLeghQ ef cd af UMaj h GdGSJNOGeGJ h GdGTHGYGJ GdeMbbI ef bQGA Gdafhf GdUMajI h JQLY GgejI gPG GdcJGH Gdi Gfg jSGYO GdbGFejf HGdGJUGd eY GdUMa aj GNJjGQ GdbhGdH GdafjI GdJMQjQjI GdJj jaVdgG GdLeghQ aj GdehVhYGJ GdeNJdaI s
(3edG(B.:267-327s
Keywords: (3GdcJGHI GdUMajIs; (3GdUMGaIs